2018
DOI: 10.1038/s41437-018-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the genetic effects of refugial isolation and range expansion in a trans-continentally distributed species

Abstract: In wide-ranging taxa with historically dynamic ranges, past allopatric isolation and range expansion can both influence the current structure of genetic diversity. Considering alternate historical scenarios involving expansion from either a single refugium or from multiple refugia can be useful in differentiating the effects of isolation and expansion. Here, we examined patterns of genetic variability in the trans-continentally distributed painted turtle (Chrysemys picta). We utilized an existing phylogeograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 84 publications
(101 reference statements)
3
22
0
Order By: Relevance
“…Recently, much emphasis in the literature has been also put on testing biologically informed models to gain insights into the taxon‐specific causal mechanisms structuring a species’ gene pool (Papadopoulou & Knowles, ; Paz et al., ; Sukumaran & Knowles, ). These conceptual and analytical advances have proven useful for generating refined hypotheses and for testing the impacts of microhabitat preferences (Massatti & Knowles, ), physiological trade‐offs (Bemmels, Title, Ortego, & Knowles, ) and climate‐induced range shifts (He et al., ; Reid et al., ) on the spatial distribution of genetic variation in numerous organisms (Hoban, ). Ultimately, this can allow better inference of biological processes that in turn are useful to predict and mitigate threats associated with various components of global change, such as warming climate and habitat fragmentation (Brown et al., ; Espindola et al., ; Estrada, Delgado, Arroyo, Traba, & Morales, ; Morrison, Estrada, & Early, ; Prates et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much emphasis in the literature has been also put on testing biologically informed models to gain insights into the taxon‐specific causal mechanisms structuring a species’ gene pool (Papadopoulou & Knowles, ; Paz et al., ; Sukumaran & Knowles, ). These conceptual and analytical advances have proven useful for generating refined hypotheses and for testing the impacts of microhabitat preferences (Massatti & Knowles, ), physiological trade‐offs (Bemmels, Title, Ortego, & Knowles, ) and climate‐induced range shifts (He et al., ; Reid et al., ) on the spatial distribution of genetic variation in numerous organisms (Hoban, ). Ultimately, this can allow better inference of biological processes that in turn are useful to predict and mitigate threats associated with various components of global change, such as warming climate and habitat fragmentation (Brown et al., ; Espindola et al., ; Estrada, Delgado, Arroyo, Traba, & Morales, ; Morrison, Estrada, & Early, ; Prates et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The important role of re-expansion dynamics has recently been highlighted in a range of different species e.g. (8,11,28), though it would be naïve to assume that the complex patterns of diversity found in real populations could be easily explained by a single mechanistic process (29). Our work highlights that, at the very least, modern population diversity and structure may have originated from a combination of different processes, each of which needs to be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…An extreme consequence of this process is gene surfing, when rare variants can become common through stochastic sampling during a founder event, and then be spread widely at high frequency during the subsequent expansion. An important role for the recolonization dynamics in shaping modern-day population structuring has been recently put forward for a trans-continentally distributed species, the painted-turtle, Chrysemys picta (11). Reid et al (11) demonstrated that, for this species, genetic differentiation during range expansion and isolation-by-distance are more likely to have driven modern-day population diversity than isolation in allopatric refugia.…”
Section: Introductionmentioning
confidence: 99%
“…At the expansion front, successive founder events lead to a fast differentiation from the source, producing a characteristic demographic signature that is distinguishable from non-spatial population growth (Excoffier et al, 2009; François et al, 2010; Peter & Slatkin, 2013; Alvarado-Serrano & Hickerson, 2018). By tracking the spatial dynamics of populations one can locate zones of climatic stability (Potter et al, 2016), track sources of population invasions (Fischer et al, 2017), and understand how genetic diversity was affected by past environmental changes (Reid et al, 2019), allowing for more robust predictions to explore classical diversification hypotheses.…”
Section: Introductionmentioning
confidence: 99%